2020
DOI: 10.3390/genes11080883
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the lncRNAs Related to Skeletal Muscle Fiber Types and Meat Quality Traits in Pigs

Abstract: The alteration in skeletal muscle fiber is a critical factor affecting livestock meat quality traits and human metabolic diseases. Long non-coding RNAs (lncRNAs) are a diverse class of non-coding RNAs with a length of more than 200 nucleotides. However, the mechanisms underlying the regulation of lncRNAs in skeletal muscle fibers remain elusive. To understand the genetic basis of lncRNA-regulated skeletal muscle fiber development, we performed a transcriptome analysis to identify the key lncRNAs affecting skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…In the current research, 47 differentially expressed lncRNAs, as well as 210 differentially expressed TUCPs and 1304 differentially expressed mRNAs were identified. The newly identified lncRNAs from rumen were shorter in length, fewer in exon number, lower in expression level and less conserved than protein-coding transcripts [ 28 ]. Integration of differentially expressed lncRNAs and DEGs found that 47 DE-lncRNAs regulated 860 DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…In the current research, 47 differentially expressed lncRNAs, as well as 210 differentially expressed TUCPs and 1304 differentially expressed mRNAs were identified. The newly identified lncRNAs from rumen were shorter in length, fewer in exon number, lower in expression level and less conserved than protein-coding transcripts [ 28 ]. Integration of differentially expressed lncRNAs and DEGs found that 47 DE-lncRNAs regulated 860 DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, denervation and cancer cachexia increase the activity of satellite cells [ 49 , 50 ], and casting and fasting decrease the number of satellite cells [ 51 , 52 ]. Recently, Li et al found that the lncRNA MSTRG.42019 was associated with skeletal muscle fiber-type switching in pigs [ 53 ]. Several lncRNAs, such as LncMyoD , SAM , H19 , and CTTN-IT1 , affect the activity of satellite cells in mice, pigs, and sheep [ 54 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle is one of the most dynamic tissues involved in a variety of biological processes 1 , and the growth and development of skeletal muscle are essential for maintaining skeletal muscle function 2 . Skeletal muscle dysfunction can lead to a variety of human muscle diseases, including muscle dystrophy, type 2 diabetes, cardiomyopathic disease, and other metabolic disorders 3 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported that the ratio of muscle fiber types could affect meat quality 11 13 . In addition, skeletal muscle is dynamic muscle tissue, the fast muscle fiber subtype (type II) and the slow muscle fiber subtype (type I) can mutually transform regulated by noncoding RNAs 2 , 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%